Drivers and barriers of seasonal influenza vaccination 2015/16 & 2019/20 to 2022/23 - a survey on why most Norwegians don't get the flu vaccine - Birgitte Klüwer; Kjersti Margrethe Rydland; Svenn-Erik Mamelund; Rebecca Nybru Gleditsch (BMC, 2024)
Abstract Background This study aimed to explore the reasons adults in the general population, influenza risk groups (RGs) and health care workers (HCWs) in Norway give for their vaccination choices and whether these reasons vary between groups or over time in order to further improve influenza vaccination coverage. Methods Respondents of a nationally representative telephone survey conducted by Statistics Norway were asked "What was the most important reason why you did/did not get vaccinated?". The question on influenza non-vaccination was included in 2016 and in 2020 to 2023 and the question on influenza vaccination in 2021 to 2023. Results The study included 9 705 individuals aged 18-79 years. Influenza vaccination coverage in the RGs increased from 20.6% in 2016 to 63.1% in 2022, before a reduction to 58.3% in 2023. Common reasons for non-vaccination were similar in all groups. The most cited reasons were "no need" for the vaccine and "no specific reason", followed by "not recommended/offered the vaccine", "worry about side effects" and "vaccine refusal". The most frequent reasons for vaccination among the general population and RGs were protection against influenza and belonging to a RG, while the most frequent responses among HCWs were being offered the vaccine at work/work in health care, followed by a desire for protection against influenza. Receiving a vaccine recommendation from a health professional was mentioned in all groups. We also observed that the proportion reporting "no need" for the vaccine decreased over time, especially among HCWs, and that the proportions reporting vaccine refusal and worry about side effects as reasons for non-vaccination were temporarily reduced during the COVID-19 pandemic. Conclusions The general population and RGs cite protection against influenza as their primary incentive for vaccination, while HCWs mainly refer to their professional role or workplace vaccination. For non-vaccination we see a similar pattern in all groups, with "no need" and "no specific reason" as the main reasons. Of note, worry about side effects and vaccine refusal is as frequent among HCWs as in other groups. Continued efforts to maintain and increase vaccine confidence are needed.